PENGGUNAAN GOOGLE CALENDAR DALAM PEMBUATAN JADWAL KEGIATAN SEKOLAH - Vickry Ramdhan; Adhityo Kuncoro; Rahman Abdillah; Fajar Erlangga (POLITEKNIK LP3I JAKARTA, 2023)
This community service activity aims to provide training to teachers on how to manage educational services through the use of the Google calendar application during this pandemic transition that can reach many parties. Data collection uses participatory observation techniques so that the team is able to observe the events that occur and obtain the information sought to answer questions that are partner’s problems. It is conducted before and during the activity. In conclusion, the use of any application in the management of school activities has advantages and disadvantages. With this socialization, teachers will no longer experience the hassle of using the Google calendar application, especially in terms of utilizing a number of features in the application and its use in making schedules or reminders for future school agendas.Keywords: Appilcation, Google Calendar, Sechedule